2019
DOI: 10.36709/jte.v4i2.13915
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of English Textbook “When English Rings a Bell” for Junior High School Grade Seven

Abstract: This research was accomplished to find out whether English textbook  “When  English  Rings A  Bell” for Junior High  School on seventh grade fulfilled each criterion of textbook evaluation criteria. The researcher used qualitative analysis as the research design. The data source was collected from English textbook “When English Rings A Bell” for Junior High School on seventh grade. The instrument of this study was textbook evaluation criteria. The researcher collected the data by using checklist to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Foundational work on the study of L2 writing strategies has investigated ESL textbooks for use within the context of the United States (Raimes, 1986). More recent work has investigated the proportion of writing strategies in EFL textbooks across the globe, such as in Japan (Kobayakawa, 2011), Jordan (Al-Qadi & Al-Qadi, 2015), Pakistan (Habib & Umar, 2017), Indonesia (Cahyati, Srijono, & Hum, 2018). A summary of these studies can be found in Table 1, which shows that these textbooks do not equally address all aspects of the writing process-with each study tending to emphasize certain components at the expense of others.…”
Section: Evaluation Of L2 Textbooks From a Micro Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Foundational work on the study of L2 writing strategies has investigated ESL textbooks for use within the context of the United States (Raimes, 1986). More recent work has investigated the proportion of writing strategies in EFL textbooks across the globe, such as in Japan (Kobayakawa, 2011), Jordan (Al-Qadi & Al-Qadi, 2015), Pakistan (Habib & Umar, 2017), Indonesia (Cahyati, Srijono, & Hum, 2018). A summary of these studies can be found in Table 1, which shows that these textbooks do not equally address all aspects of the writing process-with each study tending to emphasize certain components at the expense of others.…”
Section: Evaluation Of L2 Textbooks From a Micro Perspectivementioning
confidence: 99%
“…Research on the inclusion of prewriting strategies in textbooks addresses two main aspects. First, studies examine the types of prewriting strategies offered in textbooks, such as: freewriting, brainstorming, instructions to pose questions about a topic, journal writing (Raimes, 1986), discussion to generate ideas, the making of notes/listing (Johnston, 1996), and the collection of relevant information (Al-Qadi & Al-Qadi, 2015;Cahyati, Srijono, Hum, 2018). Second, research investigates the frequency of prewriting strategies in textbooks.…”
Section: Research On Writing Strategies Implemented In the Prewriting...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dengan demikian, teks yang berposisi di bawah dianggap lebih penting karena merupakan penjelasan atau penjabaran dari teks pertama. b. Warna biru (tosca) diasosiasikan dengan langit atau air, sehingga warna tersebut dimaknai dengan ketenangan, kemurnian, kesegaran (Krisnawati, 2005). Jika dikaitkan dengan nilai pendidikan karakter, pemilihan warna biru lembut pada gambar atau ilustrasi berhubungan dengan nilai-nilai religius yang menjunjung kemurnian dan kelembutan.…”
Section: Komposisiunclassified